EFEKTIVITAS E-MAGAZINE TERINTEGRASI AYAT AL-QUR’AN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK - Ghivari, Silvia; Rakhmawan, Aditya; Sidik, Rahmad Fajar; Retno, Ana Yuniasti; Fikriyah, Aida (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2024)
This study aims to determine the improvement of students' concept understanding. This research method is RD research with a one group pretest pottest development design. The development model used is the ADDIE model. The population of this study were all students of class VII MTsN Bangkalan with a sample of class VII-H students totaling 29 students selected through purposive sampling technique. The data collection techniques used are questionnaires, interviews, observations, and tests. 1) The results showed that the validity of the media aspect was 93.47% and the material aspect was 91.67% with a very valid category for both aspects. 2) The result of the N-Gain value of students' concept understanding is 0.75 with a high category.